Házgyár utca 1. . Házgyár Street 1 - Börzsei, Juli; Szabó, Péter (Börzsei, Juli, 2012)
Verzio9 FF Submission. Duration: 00:30:00 This delapidated block of flats used to be a factory dormitory. Today it is inhabited by people who have no other place to go. Others try to avoid going near it, and the residents themselves wish they could have moved to a better place. Squatters, homeless people and hooligans have ruined the building. The media spotlighted it as a dangerous, run-down and dirty corner of the city. The film shows a different side of the notorious building, offering a rare chance to visit local residents, each of whom shares a very personal story.